EXPLORE THE HISTORICAL SITE OF ISLAMIC HERITAGE IN SOUTHERN THAILAND - Harfiani, Rizka; Chapakiya, Suraiya; Manik, Loli Asmitasari (Proceeding International Seminar of Islamic Studies, 2024)
This research article was written with the aim of describing the historical sites of Islamic heritage in Southern Thailand. This research uses a qualitative method with a narrative type with a socio-historical approach. The data collected in this article mostly comes from literature studies, both from popular articles and from previous research, apart from that it is also based on the results of observations, interviews and documentation, where researchers directly visited these historical places. The data analysis technique uses Miles and Huberman interactive analysis, with data validity techniques using the triangulation method. The results of the research describe 6 historical site locations in Southern Thailand, namely: 1) History of the Raja Selindung Bayu Mosque, Teluban (Saiburi) Pattani; 2) History of the Telok Manok Mosque; 3) History of the Keresik Mosque (Krue Se Mosque); 4) History of the Aho Mosque; 5) History of the Langkasuka Fellowship, and 6) History of the Jami' Pattani Mosque in Thailand. The conclusion from the research results is that even though Muslims are a minority in Thailand, they are proud and continue to maintain the existence of Malay culture and the Islamic religion which has become their identity, by continuing to preserve and care for the historical sites of Islamic heritage in Thailand. South.